HETEROGENIC SERUM, AGE, AND MULTIPLICATION OF FIBROBLASTS - Carrel, Alexis (The Rockefeller University Press, 1922)
The presence in a culture medium of heterogenic serum of various concentrations exerts a definite influence on the rate of multiplication of fibroblasts. Dog serum does not inhibit the growth of See PDF for Structure chicken fibroblasts markedly until its concentration reaches 15 per cent. Beyond this figure, each increase of the concentration brings about a rapid decrease in the rate of cell multiplication. When the concentration reaches from 30 to 45 per cent, no growth takes place. The inhibiting action of cat serum begins to manifest itself at a concentration of 25 per cent and prevents cell proliferation completely at a concentration of 55 and 60 per cent. The ratio, See PDF for Equation can be taken as expressing the action of the serum on fibroblast multiplication; that is, as the growth index of the serum. See PDF for Structure The inhibiting influence of heterogenic serum was found to vary in direct ratio to the age of the animal from which it was obtained. The rate of proliferation of chicken fibroblasts was studied comparatively in media containing varied concentrations of serum from young and old animals. For each concentration of serum, the rate of growth in the serum of the old animal was expressed in relation to the rate of growth in the serum of the young animal. When cat serum was used, the curve obtained in plotting this ratio in ordinates and the serum concentration in abscissæ showed a rapid increase in the inhibiting action of the old serum as soon as the concentration reached 30 per cent. The same tests were repeated with the serum from young and old dogs. The general results were identical, although See PDF for Structure the quantitative inhibiting action of both sera was greater than that of cat serum. It may be concluded that under the conditions of the experiments: 1. Heterogenicsera inhibit and prevent the growth of chicken fibroblasts when their concentration is made to vary within certain limits. 2. A relation exists between the rate of growth of chicken fibroblasts, the concentration of the heterogenic serum, and the age of the animal from which the serum is taken. Thus, the rate of proliferation of chicken fibroblasts expressed by the growth index of the serum can be used as a means for detecting certain changes brought about by age in a heterogenic serum.